B2B e-commerce success among small and medium-size enterprises: a business network perspective - Ghobakhloo, Morteza; Tang, Sai Hong; Standing, Craig (IGI Publishing, 2015)
E-commerce (EC) success and related influencing factors have not been investigated properly in the context of small and medium-sized enterprises (SMEs), while these businesses possess very different characteristics as compared to large businesses. The purpose of this study is to provide a better and clearer understanding of business-to-business (B2B) EC value and success within SMEs, particularly in emerging economies. Rooted in the information system (IS) diffusion and success literature and organizational research background, this paper develops an integrative research model to assess the success of B2B EC among Iranian and Malaysian SMEs. To interpret the success of B2B EC, we viewed EC success dimensions and relevant determinants from the perspectives of all users at the business network unit level. The result of testing this model on 130 business network units revealed that in addition to technological characteristics of EC including information, system and service quality, different SME-related organizational determinants such as perceived usefulness of EC, top management support and commitment and EC knowledge are crucial for successful B2B EC among SMEs. The findings offer valuable insights to managers, EC/IS experts and policy makers responsible for assisting SMEs with successfully engaging in B2B EC.